Acute polyneuromyopathy with respiratory failure secondary to monensin intoxication in a dog. Issue 1 (6th December 2017) - Bosch, Luis; Bersenas, Alexa M.; Bateman, Shane
Abstract: Objective: To describe a successfully managed case of polyneuropathy and respiratory failure secondary to presumed monensin intoxication. Case Summary: A 9‐month‐old Australian Shepherd was evaluated for progressive generalized weakness and respiratory distress. Several days preceding presentation, the dog was seen playing with a monensin capsule, and had free access to a barn where the product was stored and where chewed capsules were subsequently found. The dog was presented with flaccid tetraparesis, hyperthermia, and severe respiratory distress. Bloodwork and urinalysis revealed marked increase in serum creatine kinase concentration and presumed myoglobinuria. Cardiac troponin I level was markedly increased. Management included mechanical ventilation for 5 days, fluid‐therapy, active cooling, antimicrobial therapy, analgesia, gastroprotectants, antiemetics, enteral feedings, continuous nursing care, and physiotherapy. Intravenous lipid rescue therapy was administered with lack of improvement in respiratory function and muscle strength. The patient completely recovered and was discharged after 12 days of hospitalization. New or Unique Information Provided: Monensin intoxication should be considered in the differential diagnosis of acute polyneuromyopathy and respiratory failure in dogs with access to this compound. Respiratory failure secondary to monensin intoxication does not necessarily carry a poor prognosis if mechanical ventilation can be provided as a bridge until return of respiratory function is achieved.